Pemberian Pinjaman Dana Bergulir Tanpa Bunga Dalam Upaya Meningkatkan Perekonomian dan Usaha Mikro Kecil dan Menengah (UMKM) di Kabupaten Bandung - Rihhadatul ‘Aisy , Alya; Karniawati, Nia (LPPM STISIP IMAM BONJOL, 2024)
Bandung Regency is an area with a population of 3.6 million people. With such a large population, Bandung Regency has significant economic potential. The economy of Bandung Regency is supported by the agriculture, plantation, industry and tourism sectors. One of the key elements in the local economic structure is Micro, Small and Medium Enterprises (MSMEs). The role of MSMEs is important in moving the wheels of the local economy, creating jobs and making a positive contribution to regional development. The purpose of this research is to analyze the interest-free revolving fund loan program in an effort to improve the economy and Micro, Small and Medium Enterprises (MSMEs) in Bandung Regency. The results showed that the Bandung Regency Government launched an Interest-Free Revolving Fund Loan Program of Rp 70 billion. However, in its implementation there are still obstacles including the difficulty of borrowers to pay loans, so that funds are not rolled back quickly.